Arus Kas Bebas dan Nilai Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Teguh Erawati; Fransiska Ayu Novita Jedaru (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study is to investigate the effect of free cash flow and firm size on firm value. The population of this study is manufacturing companies listed on the Indonesian Stock Exchange (IDX) during the period 2017-2019. The sampling technique used an objective sampling method. The total sample satisfying the criteria was 54 companies, and SPSS statistical application was used as the analysis method. The independent variables in this study are free cash flow and firm size. The dependent variable in this study is the enterprise value calculated using Tobin's Q method. The results of this study show that free cash flow has a negative effect on corporate value. Firm size has a positive effect on firm value. Keywords: free cash flow, company size, company value